Knowledge-based entrepreneurship in Poland - Richard Woodward; Deniz Eylem Yörük; Patryk Koć; Wojciech Pander (Center for Social and Economic Research (CASE), 2010)
The importance of new firm creation in the post-Communist economies of East Central Europe (ECE) has been subject to extensive research. This paper focuses on an area of entrepreneurship which has received relatively little attention in the transition economy context but which is of particular importance for the modernization of the transition economies: knowledge-based entrepreneurship (KBE), or new firm creation in industries considered to be science-based or to use research and development (R&D) intensively. We begin by sketching the situation in Poland's small and medium-sized business sector, then proceed to outline the National Innovation System, with particular attention devoted to the question of finance and policy initiatives. We then turn to the analysis of a series of case studies in industries such as information technology, life sciences, digital navigation technology (mobile mapping systems), aviation, and other industries considered to be science-based or R&D-intensive. Among the issues treated are the resources and strategies.
Keywords: L26; O31; O52; P27; 330; Knowledge-based economy; entrepreneurship; transition; post-communist; Wissensgesellschaft; Innovation; Forschung; Informationstechnik; Entrepreneurship-Ansatz; KMU; Systemtransformation; Polen